How does IT affect design centricity approaches: Evidence from Spain’s smart tourism ecosystem - Arenas, Álvaro; Goh, Jie Mein; Urueña, Alberto (Elsevier, 2019)
Little or no prior work has examined how information technology enables the development of a design centered digital ecosystem. To examine this research question, we employ a capabilities lens and identify the pathways through which IT drives the development of a design centric smart tourism ecosystem. We analyzed archival data and data collected from interviews conducted in Spain, a country which has embarked on smart destinations projects and topped the World Economic Forum’s Travel and Competitiveness Index. From our analysis, we delineate and identify specific IT-enabled capabilities important for a country implementing smart tourism projects. We find that many of the IT resources available help develop key capabilities necessary for creating a design centric smart tourism ecosystem.
Keywords: Smart tourism; Design centric; IT capabilities; Tourism ecosystem; 53 Ciencias Económicas::5312 Economía sectorial::5312.90 Economía sectorial. Turismo; ODS 11 - Ciudades y comunidades sostenibles